Strategy for Overcoming Forgetful Children - Daviq Chairilsyah (LPPM Universitas Pahlawan Tuanku Tambusai, 2020)
Forgetfulness individuals are commonly linked with old age, even though many young people are also facing situation easy to forget. Forgetfulness could happen to anyone, including early childhood. This article used a literature review method that provided children with a full and detailed explanation of the 'forgetful' topic. Forgetfulness children have two characteristics, namely normal and abnormal. There are several causes that can trigger a child to become forgetfulness; fatigue, malnutrition, stress, under certain medications and health issues. There are methods that teachers and parents can try to improve their memory, teaching children to be independent, asking some questions to stimulate their memories, making a daily timetable, and praising when children are not forgetfulness, doing discipline programs, and buying toys that can practice memory and some reading programs. It is expected that gradually the child's memory will reoccurrence to normal. Every parent must monitor their child's growth and development, if the child experiences normal forgetfulness the parents can cope by themselves, if the child experiences an abnormal forget, the parents must be alert and consult with a doctor or psychologist in order to overcome this problem early and effectively.